Calculation of Available Surface Water Resources in Xijiang River Basin Based on Ecological Water Demand Inversion - ZHANG Xiaolin; ZHANG Yimin; CHEN Chang; CHEN Hao (Renmin Zhujiang)
The utilizable amount of surface water resources is the threshold value of comprehensive utilization of water resources obtained under the condition of overall living, production, and ecological water use. This concept is not unified and the calculation methods are different. The purpose of this study is to apply a relatively simple and convenient method, indirect algorithm, to calculate the surface water resources availability and reduce the difficulty of basic data collection and calculation process as much as possible. The method involves comprehensive considerations of the natural runoff situation and distribution characteristics of the basin, as well as the development, utilization, and planning of current water resources. Starting from the needs of the ecosystem, it aims to calculate the usable amount of surface water resources indirectly by calculating the target ecological water demand in the river course. Taking the Xijiang River Basin as an example, the calculated annual average utilizable amount of surface water resources from 1956 to 2016 is 45.97 × 109 m3, and the utilizable rate is 20%. Through a rational analysis, the available amount of surface water resources in the Xijiang River Basin can satisfy the increased water demand out of the basin in 2030, a target year as part of the long-term planning for the Xijiang River Basin, and meanwhile ensure ecological water demand of the basin, which can be an important basis for the revision of basin or regional planning, water allocation and scheduling, and the revision of total control indicators in the future.